Designing and developing a 2D animation film titled "The Chernobyl Nuclear Power Plant Disaster" to communicate and raise awareness of the catastrophic consequences of nuclear power plants - พีรพัฒน์ พีรพัฒน์; วิจิตรสกุลรัตน์ วสุพงศ์; โพธิ์ขี ธนกฤต; ดีเจริญชิตพงศ์ จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research titled “The Development of a Two-Dimensional Animation Media on the Topic of the Chernobyl Nuclear Power Plant Disaster” aims to: 1) study the design and production process of two-dimensional animation media on the topic of the Chernobyl nuclear power plant disaster; 2) develop educational media that provides knowledge about the way of life of residents during the explosion of the Chernobyl nuclear power plant; and 3) disseminate the media through the YouTube platform. The sample group consisted of 40 members of the general public who were interested in the Chernobyl incident and had viewed the two-dimensional animation media. The results of the study revealed that: 1) the evaluation of content quality by content experts showed an overall mean score of 3.83 with a standard deviation (S.D. = 1.15), which was interpreted as being at a moderate level; 2) the evaluation of media quality by media experts showed an overall mean score of 3.71 with a standard deviation (S.D. = 1.10), which was also interpreted as being at a moderate level; and 3) the satisfaction evaluation of general viewers who were interested in the Chernobyl incident and had watched the media showed an overall mean score of 3.94 with a standard deviation (S.D. = 0.88), indicating a moderate level of satisfaction.